2008
DOI: 10.1073/pnas.0805135105
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle size and surface properties determine the protein corona with possible implications for biological impacts

Abstract: Nanoparticles in a biological fluid (plasma, or otherwise) associate with a range of biopolymers, especially proteins, organized into the ''protein corona'' that is associated with the nanoparticle and continuously exchanging with the proteins in the environment. Methodologies to determine the corona and to understand its dependence on nanomaterial properties are likely to become important in bionanoscience. Here, we study the long-lived (''hard'') protein corona formed from human plasma for a range of nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

62
2,340
10
13

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 2,682 publications
(2,465 citation statements)
references
References 21 publications
62
2,340
10
13
Order By: Relevance
“…Furthermore, in relation to recent findings, it would be interesting to see if the difference between serum and blood might be related to a different composition of the protein corona. 5 In any case, our results indicate the urgent need for methods that can analyze particle size in undiluted biological media.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, in relation to recent findings, it would be interesting to see if the difference between serum and blood might be related to a different composition of the protein corona. 5 In any case, our results indicate the urgent need for methods that can analyze particle size in undiluted biological media.…”
mentioning
confidence: 81%
“…For instance, recent investigations have shown that typically a biopolymer corona is formed around nanoparticles in plasma, depending on their composition, size, and surface charge. 5 Since this corona alters their outer surface, it can influence the effective nanoparticle behavior. 6 Apart from their surface properties, a crucial parameter is the effective size of nanoparticles in the blood circulation because it directly influences their clearance and biodistribution, [7][8][9][10] as well as their subsequent uptake and processing by target cells.…”
mentioning
confidence: 99%
“…However, it should be noted that even under serum-free conditions some proteins can be found on the NPs after incubation with cells for some time, probably originating from cell secretions and cell damage 35 . Part of the proteins, the so-called "hard corona" associated with the NPs are so strongly bound to the NPs that NP-protein complexes can be isolated from a NP dispersion 19 and re-suspended in serum free medium. In this way it is possible to demonstrate the effect of the hard corona protein layer on NP uptake and exclude other effects due to the presence of serum in the medium, such as crowding and/or competition for the cell membrane and membrane receptors by the serum proteins.…”
Section: Kinetics Of Nanoparticle Uptakementioning
confidence: 99%
“…[14][15][16] However, NPs dispersed in a biological fluid are rapidly covered by biomolecules, such as proteins and lipids, forming a biomolecular 'corona' that effectively screens the bare NP surface. [17][18][19][20][21][22] When cells are exposed to NPs it is therefore, in realistic circumstances, typically not the bare NP surface that interacts with the cell but the NP-biomolecular corona complex. [23][24][25] Consequently, it becomes interesting to correlate NP uptake not to properties of the bare NP, but to properties of the NP-biomolecular corona complex.…”
Section: Introductionmentioning
confidence: 99%
“…However, anionic PAA‐NPs could still mediate cell toxicity by interacting with blood proteins, creating protein coronas (i.e., the protein adsorption layer that forms around NPs26) that influence the fate and transport of NPs within circulation and into the cells of animals.…”
Section: Discussionmentioning
confidence: 99%